Commemorating Race and Empire in The First World War Centenary - Wellings, Ben; Sumartojo, Shanti (Sociétés contemporaines, 2018)
First World War commemoration in Europe has been framed as a moment of national trial and as a collective European tragedy. But the 'Great War for Civilisation' was more than just a European conflict. It was in fact a global war, a clash of empires that began a process of nationalist agitation against imperial polities and the racisms that underpinned them in Asia, Africa and beyond. Despite the global context of Centenary commemorative activity these events remain framed by national and state imaginaries and ones in which the ideas about nation, race and imperialism that animated and dominated men and women during the Great War sit uncomfortably with modern sensibilities. By drawing on original archival research, translations from French and Mandarin into English and by employing multidisciplinary conceptual frames of analysis, this exciting and innovative volume explores how race and empire, and racism and imperialism, were commemorated during the First World War Centenary.